Face-to-face communication over the Internet : emotions in a web of culture, language, and technology - Kappas, Arvid; Kramer, Nicole C. (Cambridge, UK : Cambridge University Press, 2011)
'Social platforms such as MySpace, Facebook and Twitter have rekindled the initial excitement of cyberspace. Text based computer-mediated communication has been enriched with face-to-face communication such as Skype, as users move from desk tops to laptops with integrated cameras and related hardware. Age, gender and culture barriers seem to have crumbled and disappeared as the user base widens dramatically. Other than simple statistics relating to e-mail usage, chatrooms and blog subscriptions, we know surprisingly little about the rapid changes taking place. This book assembles leading researchers on non-verbal communication, emotion, cognition and computer science to summarize what we know about the processes relevant to face-to-face communication as it pertains to telecommunication, including video-conferencing. The authors take stock of what has been learned regarding how people communicate, in person or over distance, and set the foundations for solid research helping to understand the issues, implications and possibilities that lie ahead'--Provided by publisher.
Introduction: electronically mediated face-to-face communication: issues, questions, and challenges / Arvid Kappas and Nicole C. Kr$1#-m(Ber --s Part 1. General Aspects of Visual Cues in CMC: 1. Visual cues in computer-mediated communication: sometimes less is more / Joseph B. Walther; 2. To be seen or not to be seen: the presentation of facial information in everyday telecommunications / JosMiguel Ferndez-Dols and Pilar Carrera; 3. Gendered social interactions in face-to-face and computer-mediated communication / Agneta Fischer -- Part 2. Video- and Avatar-Based Communication: 4. Nonverbal communication and cultural differences: issues for face-to-face communication over the internet / Pio Enrico Ricci Bitti and Pier Luigi Garotti; 5. Video-linking emotions / Brian Parkinson and Martin Lea; 6. Impact of social anxiety on the processing of emotional information in video-mediated interaction / Pierre Philippot and Cine Douilliez; 7. Facing the future: emotion communication and the presence of others in the age of video-mediated communication / Antony S.R. Manstead, Martin Lea, and Jeannine Goh; 8. Virtual gestures: embodiment and non-verbal behavior in computer-mediated communication / Gary Bente and Nicole C. Kr$1#-m(Ber --s Part 3. Emotions and Visual Cues in HCI: 9. Emotions in human-computer interaction / Veikko Surakka and Toni Vanhala; 10. Embodiment and expressive communication on the internet / Elisabeth Oberzaucher, Karl Gramme,r and Susanne Schmehl.
Includes bibliographical references and index.
Keywords: Social networks; Internet -- Social aspects; Teleconferencing